Midwives' knowledge and practice of Respectful Maternity Care: a survey from Iran - Maryam Moridi; Farzaneh Pazandeh; Barbara Potrata (BMC, 2022)
Abstract Background In the past decade, countries worldwide aimed to evaluate the quality of childbirth care and reduce the high rates of disrespect and abuse during childbirth. Few studies have attempted to identify providers' characteristics associated with respectful maternity care quantitatively. This study aims to evaluate midwives' knowledge and practice of respectful maternity care (RMC). Methods A cross-sectional study was carried out in 15 teaching and non-teaching hospitals in Tehran, Iran. The hospitals were selected by using a cluster sampling design. Midwives' Knowledge and Practice of Respectful Maternity Care scale (MKP-RMC) was administered to 250 midwives working in maternity units at study hospitals. The data were analysed by statistics package for social science (SPSS, version 21.0, Chicago, IL). Results Findings demonstrated that the mean score for knowledge and practice of midwives were 20.96 ± 3.54 and 101.64 ± 11.49, respectively. Also, in both knowledge and practice scales, midwives had the highest score in "providing safe care' domain and the lowest score in "preventing mistreatment" domain. Conclusion Our findings showed that for Iranian midwives, providing care to preserve mothers' and their babies' wellbeing is more critical than preventing maternal mistreatment, resulting from the importance of the care provision in the Iranian healthcare system. Promoting midwives' knowledge and practice through developing a tailored educational program to prevent mistreatment and providing emotional support alongside physical care is recommended.